Информатика пəнін оқытуда ойын технологияларын қолдану - Курманбаева, М. Е. (My University, 2016)
For the productive way of student’s work at the lessons it is necessary to use active methods of teaching. One of them is games. It helps to stimulate student’s interest to the subject and makes the process of studying active and realistic. Also it develops the skills of working in a team, productive thinking, memory, attention. Moreover, such games help to explain your own opinion on the given subject.
Keywords: creative thinking; game; computer technologies